Decomposing the Variance of Consumer Ratings and the Impact on Price and Demand - Zimmermann , Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barry (Information Systems Research)
Consumer ratings play a decisive role in purchases by online shoppers. Although the effect of the average and the number of consumer ratings on future product pricing and demand have been studied with some conclusive results, the effects of the variance of these ratings are less well understood. We develop a model which considers durable goods that are characterized by three types of attributes: search attributes, experience attributes, and transformed attributes the latter are conventional experience attributes that are transformed by consumer ratings into attributes that can be searched. Using informed search attributes to refer to the combination of search attributes and transformed attributes, we consider two sources of variance of consumer ratings: taste differences about informed search attributes and quality differences in the form of product failure representing experience attributes. We find that (i) optimal price increases and demand decreases in variance caused by informed search attributes, (ii) optimal price and demand decrease in variance caused by experience attributes, and (iii) by holding the average rating as well as the total variance constant, for products with low total variance price and demand increase in the relative share of variance caused by informed search attributes. Counter to intuition, we demonstrate that risk averse consumers may prefer a higher priced product with a higher variance in ratings when deciding between two similar products with the same average rating. Finally, our model provides a theoretical explanation for the empirically observed j-shaped distribution of consumer ratings in e-commerce that differs from established explanations.

Beschreib mir deine Wohnung und ich sag dir wer du bist - Eine explorative Analyse von Gastgeberpersönlichkeiten auf Airbnb - Müller, Michelle; Gutt, Dominik; Neumann, Jürgen (Multikonferenz Wirtschaftsinformatik (MKWI) 2018)

A Duration Model Analysis of Consumer Preferences and Determinants of Video Game Consumption - Kaimann, Daniel; Stroh-Maraun, Nadja; Cox, Joe (Journal of Consumer Behaviour)

Variety in the video game industry: An empirical study of the Wundt curve - Kaimann, Daniel; Stroh-Maraun, Nadja; Cox, Joe (Managerial and Decision Economics)

Wenn Marketing mobil wird - Ein Überblick zum Einfluss mobiler Geräte auf digitale Märkte - Reger, Alexander

Höhere Verkaufszahlen durch gute Online-Bewertungen - Ein Literaturüberblick - Tran, Viet Huy

Eine experimentelle Untersuchung der Wahrnehmung professioneller Online Bewertungen - Mues, Raphael

Sharing is Caring - Ein Literaturüberblick über die Sharing Economy - Dierkes, Johannes

Anwendung von verhaltenspsychologischen Theorien zur Steigerung rechtskonformer Einverständniserklärungen im E-Mail Marketing unter Berücksichtigung der neuen DSGVO-Richtlinien - Heukrodt, René

Gap Theory of Curiosity - Darstellung des aktuellen Forschungsstands und Untersuchung des Einflusses von Neugierde auf Job Performance auf einer Crowdsourcing-Plattform - Werning, Christian

Was bewegt Kunden auf Online-Plattformen? - Eine semantische Analyse von Online-Bewertungen mittels Latent Dirichlet Allocation - Werner, Timur Andreas Eduard Wolfgang

Zu Hause ist es am schönsten? Eine deskriptive Analyse des Online-Bewertungsverhaltens von Einheimischen und Reisenden - Jongen, Marvin Alexander

Möglichkeiten und Grenzen des Einsatzes der Crowd zur Ideenbewertung - ein klassifizierender Literaturüberblick - Filges, Lukas Leif

Der Umgang mit mobilen Konsumenten - Ein Literaturüberblick zum Einfluss mobiler Geräte auf digitale Märkte - Lappe, Annika

Heute schon bewertet? - Eine deskriptive Analyse der dynamischen Entwicklung von Online-Bewertungen - Schürmeyer, Johannes

Beim Einkauf hört die Freundschaft auf? - Eine statistische Analyse von digitalisierten Kundenbewertungen unter Berücksichtigung sozialer Beziehungen - Krüger, Noah

Herz über Kopf? Wie emotionale und neutrale Schreibstile darüber entscheiden, ob eine Online Bewertung hilfreich ist - Müller, Michelle

Immer J-Shape? Eine deskriptive Analyse von Online-Produktbewertungen am Beispiel Amazon - Brennig, Katharina

"War diese Rezension für Sie hilfreich?" - Ein Literaturüberblick über die Treiber hilfreicher Online-Bewertungen - Santüns, Jan

Vom Umgang mit der Digitalisierung von Kundenmeinungen - Ein Theorieüberblick zur strategischen Bedeutung von Online-Bewertungen - Metzner, Niklas